2018
DOI: 10.4103/sajc.sajc_187_17
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic salpingectomy and ovarian cancer: An evidence-based analysis

Abstract: Introduction:One of the ovarian carcinogenesis theories was the presence of premalignant cells in the epithelium of the fallopian tube. Therefore, the prophylactic salpingectomy during benign gynecological surgery is now expected as the attempt to reduce the ovarian cancer incidence. We studied the effect of prophylactic bilateral salpingectomy (PBS) in reducing the ovarian cancer incidence.Methods:This evidence-based report resulted from critical appraisal of 5 articles. It is aimed to answer our clinical que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…[252][253][254] Salpingectomy during hysterectomy is recommended to decrease the risk of high-grade serous ovarian carcinoma. 255 Ovarian preservation is not recommended in patients with cancer family history involving ovarian cancer risk (eg, BRCA mutation, Lynch syndrome, etc), but oocyte cryopreservation might be considered. 256 Recommendations ► Ovarian preservation can be considered in pre-menopausal patients aged <45 years with low-grade endometrioid endometrial carcinoma with myometrial invasion <50% and no obvious ovarian or other extra-uterine disease (IV, A).…”
Section: Recommendationsmentioning
confidence: 99%
“…[252][253][254] Salpingectomy during hysterectomy is recommended to decrease the risk of high-grade serous ovarian carcinoma. 255 Ovarian preservation is not recommended in patients with cancer family history involving ovarian cancer risk (eg, BRCA mutation, Lynch syndrome, etc), but oocyte cryopreservation might be considered. 256 Recommendations ► Ovarian preservation can be considered in pre-menopausal patients aged <45 years with low-grade endometrioid endometrial carcinoma with myometrial invasion <50% and no obvious ovarian or other extra-uterine disease (IV, A).…”
Section: Recommendationsmentioning
confidence: 99%
“…Screening tests before the operation showed no abnormalities, including PT and APTT (Table 1) and liver functions. She wished to receive an early hysterectomy, and then she underwent an abdominal hysterectomy and bilateral salpingectomy (Figure 1(B)) for reducing the future ovarian cancer incidence [12], after administering GnRH antagonist for one month. The operation for 121 minutes was performed as usual, and the blood loss was 100 g (ml).…”
Section: Case Reportmentioning
confidence: 99%
“…It has been hypothesized previously that the fallopian tubes are very likely to be the origin of high-grade serous cancers ( 6 ) , and thus, prophylactic or opportunistic salpingectomy at the time for hysterectomy and other benign procedures may be beneficial. The incidence of ovarian cancer among women who had undergone prophylactic salpingectomy along with hysterectomy for benign condition was found to be reduced to 30-64% ( 7 ) . In addition, a large body of evidence revealed that prophylactic bilateral salpingectomy had no significant negative effect on the ovarian function, quality of life, sexuality, surgery duration, and cost-effectivity ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ovarian cancer among women who had undergone prophylactic salpingectomy along with hysterectomy for benign condition was found to be reduced to 30-64% ( 7 ) . In addition, a large body of evidence revealed that prophylactic bilateral salpingectomy had no significant negative effect on the ovarian function, quality of life, sexuality, surgery duration, and cost-effectivity ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%